Job performance among enforcement staff in northern Malaysia: a case of JPJ Seberang Jaya, Penang, Malaysia / Anis 'Amirah Razali ... [et al.] - Razali, Anis 'Amirah; Ahmad, Noorzaihaini; Noordin, Nazmi@Nazni (2021)
Job performance among employees is very crucial in order to ensure the success of one organization. According to Anitha (2014), job performance is referring to the output achieved, and completion of work made by the employees in every organisation. There are a lot of factors that contribute to job performance, among them are training, motivation and working environment. Various studies conducted stated that those three factors do bring impacts towards job performance of employees. Besides a study by Batau and Mohamed (2016, as cited in Mohamad Nor, Haji Mohamed, Mohamed and Che Hassan, 2020) mentioned that bad working environment, lack of training and no recognition practiced by the public sector are among the reasons why civil servants are not committed in performing their work which resulted in low job performance.